Christmas Disease: Diagnostic Approaches, Treatment Options and Comparison Study with Haemophilia A (Jagannath University Journal of Science, 2025)
Haemophilia B or Christmas disease is a genetic bleeding disease defined by a deficiency of factor IX of blood clotting leading to prolonged bleeding and increased risk of hemorrhagic events. Haemophilia A, the more common form involves a deficiency of clotting factor VIII. Traditional management for both types primarily relies on factor replacement therapy which involves administering the respective clotting factors to treat bleeding episodes or for prevention. While effective this approach requires frequent infusions and can lead to the development of inhibitors in some patients. Recent advancements in gene therapy offer promising alternatives aiming to address the underlying genetic defects by delivering functional copies of the factor VIII or IX genes. This innovative approach has the potential for long-lasting effects reducing the need for ongoing factor infusions and improving the quality of life for patients. This review discusses the current management strategies for Haemophilia A and B comparing established factor replacement therapy with emerging gene therapy techniques, highlighting their benefits, limitations and future directions in the treatment landscape for both disorders.Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 86−98